115k views
0 votes
Find the derivative of 3e^y+x=y

1 Answer

6 votes

You have the following function:


y=3e^y+x

Derivate implictly the previous expression, as follow:


y^(\prime)=3e^yy^(\prime)+1

Where you have used that:


(e^y)^(\prime)=e^yy^(\prime)

Then, the implicit derivative of the given expression is:


y^(\prime)=3e^yy^(\prime)+1

Next, solve for y' as follow:


\begin{gathered} y^(\prime)-3e^yy^(\prime)=1 \\ (1-3e^y)y^(\prime)=1 \\ y^(\prime)=(1)/(1-3e^y) \end{gathered}

User Ashishssoni
by
5.2k points